A STRUCTURE AND HISTOMORPHOMETRY OF BALI DUCK TESTES IN THE GROWER PHASE - Ni Made Santi Rahayu Adiari; Ni Luh Eka Setiasih; I Putu Sampurna; Ni Ketut Suwiti; Ni Nyoman Werdi Susari; I Ketut Suatha (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Testes are male reproductive organs which are responsible for producing spermatozoa and steroid hormones. This study aims to determine the histology and histomorphometry structure of bali duck testes in the grower phase at the age of 12 weeks in one of the farms in Mengwi District, Badung Regency. The number of samples used in this research was 10 male bali ducks that were in good health. There are two examination methods carried out, namely the qualitative descriptive anatomical structure and histology examination method and the quantitative histomorphometry examination method of bali duck testicles which are analyzed using the One-Sample T-test with a confidence level of 95%. The results of this study show the anatomical structure of the bali duck testicles which are located in the abdominal cavity, between the kidneys and the lungs. The pair of testicles have the shape of a bean and are cream colored. The results of research on the histological structure of bali duck testes consist of seminiferous tubules, interstitial tissue, leydig cells, and tunica albuginea. The results of histomorphometry measurements of bali duck testes showed that the wall thickness of the seminiferous tubules was 23.6760 ± 1.4425 (µm), the number of seminiferous tubules was 421.1000 ± 56.1396 and the thickness of the tunica albuginea was 29.5000 ± 5.048 (µm). Considering the importance of knowledge about the structure of bali duck testicles, it is recommended for future researchers to examine the structure and histomorphometry of bali duck testicles at different ages in the growing phase.